Study protocol of a proposed Neurofeedback-Assisted Mindfulness Training Program on symptoms of anxiety and psychological distress associated with smartphone use in young adults: a randomized controlled trial - Fernandez-Crespo, Mei; Recio-Rodriguez, Jose I.; Lee, Hsin-Chien; Alonso-Dominguez, Rosario; Montejo, Angel L.; Hernandez-Gonzalez, Laura; Iglesias Sierra, Virginia; Rihuete-Galve, Maria I. (Frontiers in Public Health, 2024)
Background: Nomophobia is a specific phobia characterized by the appearance of anxiety, nervousness, discomfort and distress when the mobile phone is not used and is considered an emerging public health problem because of the negative consequences on the physical and mental health of young people and adolescents, especially women. Neurofeedback-Assisted Mindfulness Training Programs may prove beneficials for improving self-control abilities, a key ability in addressing addictive behaviors. The main objective of this study is to evaluate the impact, in a young population aged 18-35 years, of an intervention based on Neurofeedback-Assisted Mindfulness Training Program (NAMTP) on disorders associated with problematic use of mobile phones. The effect of the intervention on the total score in the nomophobia test and habits of internet and social network use, as well as on signs of depression, anxiety and stress will be analyzed. As a secondary objective, the effect of the intervention on signs of insomnia will be analyzed. Methods and Design: Randomized, controlled clinical-trial with two-parallel groups. 40 young adults (18-35 years) will be included and randomly assigned to Intervention Group-NAMTP or Control Group (CG). The NAMTP will include a total of 25 sessions (2-3/week) during 3-months. Each session will have a duration of 10/15 minutes. The instrument to be used for the neurofeedback sessions is MUSE® (InteraXon Inc.). Study variables will be collected at the baseline visit and at the final visit (3-months after randomization). During these visits, questionnaires will be administered to evaluate the main and secondary variables that will include the Smartphone Addiction Scale-Short Version, Nomophobia Questionnaire, Depression, Anxiety and Stress Scale 21-item (DASS-21) and Athens Insomnia Scale. Discussion: This trial will make an important contribution to the need for evidence of effective education programs and other primary care interventions through new non-invasive interventions in reducing the risk of developing addictions to new technologies and alleviating the symptoms of discomfort associated with this problem. Ethics and Dissemination: The project was approved by the Clinical Research Ethics Committee of the Salamanca Health Area (CEIm Code: PI 2023 07 1340). Clinical Trial Registration: ClinicalTrials.gov, http://www.Clinicaltrials.gov/ct2/show/NCT06188910